Clinicians’ criteria for fetal moral status: viability and relationality, not sentience - Campo-Engelstein, Lisa (Journal of medical ethics, 2024)
The antiabortion movement is increasingly using ostensibly scientific measurements such as ‘fetal heartbeat’ and ‘fetal pain’ to provide ‘objective’ evidence of the moral status of fetuses. However, there is little knowledge on how clinicians conceptualise and operationalise the moral status of fetuses. We interviewed obstetrician/gynaecologists and neonatologists on this topic since their practice regularly includes clinical management of entities of the same gestational age. Contrary to our expectations, there was consensus among clinicians about conceptions of moral status regardless of specialty. First, clinicians tended to take a gradualist approach to moral status during pregnancy as they developed and viewed viability, the ability to live outside of the uterus, as morally significant. Second, in contrast to ‘fetal pain’ laws and philosophical discussions about the ethical salience of sentience, the clinicians in our study did not consider the ability to feel pain as a morally relevant factor in moral status determinations. Third, during previability and perviability, clinicians viewed moral status as a personal value decision, which should be made by pregnant people and parents of neonates.